COMBINED IMPACT OF PRIMARY-SECONDARY RATIO AND EXCESS AIR ON COAL-FIRED POWER PLANT PERFORMANCE - Darmadi, Djarot; Yuliati, Lilis; Siswanto, Eko; Talice, Marco (Journal of Applied Engineering Science, 2024)
The primary-secondary air ratio is believed to impact both the combustion process and the overall performance of a power plant. This study aims to investigate how an increase in the primary-secondary air ratio affects the performance of a power plant located in north Gorontalo, South Sulawesi, Indonesia, using a GateCycle model. We conducted simulations of 48 variations based on three primary-secondary ratio values (PA-SA) to determine the optimal proportion of PA-SA. Our findings indicate that the optimal PA-SA ratio under stoichiometric conditions was 25-75%, resulting in a total cost of 108.03 million Rupiah per hour with a fuel burn rate of 22756 kg/h. When operating with 10% excess air, the optimal PA-SA ratio remains 25-75%, and the fuel flow and total cost were 22947 kg/h and 108.94 million Rupiah, respectively. Similarly, under 20% excess air, the optimal PA-SA ratio was also 25-75%, with a fuel flow rate and total cost of 23144 kg/h and 109.87 million Rupiah, respectively.